Advertisement Remove all ads

2y3 − 5y2 − 19y + 42 - Mathematics

Answer in Brief

2y3 − 5y2 − 19y + 42

Advertisement Remove all ads

Solution

Let f(y) =2y3 − 5y2 − 19y + 42 be the given polynomial.

Now, putting  y=2,we get

`f(2) = 2(2)^3 - 5(2)^2 - 19(2) + 42`

        ` = 16 - 20 - 38 + 42 = -58 + 58`

        ` = 0`

Therefore, (y - 2)is a factor of polynomial f(y).

Now,

`f(y) = 2y^2 (y-2) - y(y - 2) -21(y - 2)`

` = (y -2){2y^2 - y - 21}`

` = (y-2){2y^2 - 7y + 6y - 21}`

` = (y-2)(y + 3)(2y - 7)`

Hence  (y - 2),(y+3) and (2y - 7) are the factors of polynomial f(y).

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 6 Factorisation of Polynomials
Exercise 6.5 | Q 10 | Page 33
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×